URGENSI PENDIDIKAN SIFAT MALU DALAM HADITS (Telaah Hadits Imran Ibn Husain tentang Sifat Malu dalam Kitab Musnad Ahmad Ibn Hanbal) - Sauri, Supian (Universitas Islam Sultan Agung, 2019)
In the hadith of the Prophet explained one of the attributes called the term al-haya '. The nature of al-haya â€™is translated in Indonesian with the meaning of shame. Most people assume the nature of shame is a bad trait that should be kept away from someone's personal. But the shame is actually recommended by the Prophet because it is a good quality as stipulated in the hadith of Imran Ibn Husain, narrated by Ahmad Ibn Hanbal. This study aims to provide an explanation of the nature of shame mentioned by the Prophet as one of the good qualities. The conclusion of this study is the answer for people who still have the notion that shame is a bad trait that must be abandoned. The nature of shame is very urgent in Islamic education that should be fostered by all Muslims. That is due to the nature of shame can contribute to education, among others: 1) Education in shame can foster human ability to maintain the mind; 2) Keeping away actions that consume things that are prohibited; 3) Always remember death; 4) Become a person who is zuhud; 5) Contribute to the education of faith; 6) Education to decorate and beautify yourself with commendable qualities namely shame; 7) Human education to achieve the love of Allah.Â Keywords: Hadith, Prophet, Imran, Embarrassed, Education